Kadencyjność funkcji prezydenta miasta/burmistrza/wójta gminy w poglądach elektoratu partii politycznych - Widera, Zbigniew (Political Preferences, 2013)
Local and regional government are complex organizations, operating under varying environmental conditions. Their functioning and development depend on factors both internal and external. Environment creates conditions in the form of development opportunities and threats. More and more business in the management and administration of less exclusively defined area. More and more thinking about demanding customer service that is citizen (voter) and less to treat him as an object of local government influence. Important in the process of building a decision (both for the policy and for the electorate) is appropriate communication. Building belief in the power and usefulness of the current regulations that constitute its presence is convinced of its usefulness and as such goes fitness for a particular time basis. Political communication is an appropriate platform for exchange between politicians and the public, the potential buyers of the product. It serves communication and competition between political parties which issues its product to the market policy. Political communication is not only one of the mechanisms of political marketing, but it is an important plane relationship between the government and the public, allowing both parties to the transaction on the political market to obtain the relevant information of interest and sellers. This is done in analogy to the economic market where clarity is precise acceptance of the offer by the fact of its acquisition or rejection. Marketing communication in professional services is an issue extremely important and unique (specific), as the basis for her client builds their expectations of intangible product that no communication could then be created. In other words, communication is carried out in a company providing services in order to realize the benefits as well as to attract new customers.